Two Gingival Cell Lines Response to Different Dental Implant Abutment Materials: An In Vitro Study - Muataz A. Osman; Evgeny Kushnerev; Rasha A. Alamoush; Kevin. G. Seymour; Julian M. Yates (MDPI AG, 2022)
Objectives: This study aimed to investigate the response of human gingival fibroblasts (HGFB) and human gingival keratinocytes (HGKC) towards different dental implant abutment materials. Methods: Five materials were investigated: (1) titanium (Ti), (2) titanium nitride (TiN), (3) cobalt-chromium (CoCr), (4) zirconia (ZrO2), and (5) modified polyether ether ketone (m-PEEK). Both cell lines were cultured, expanded, and seeded in accordance with the protocol of their supplier. Cell proliferation and cytotoxicity were evaluated at days 1, 3, 5, and 10 using colourimetric viability and cytotoxicity assays. Data were analysed via two-way ANOVA, one-way ANOVA, and Tukey's post hoc test (p < 0.05 for all tests). Results: There was a statistically significant difference in cell proliferation of HGKC and HGFB cells in contact with different abutment materials at different time points, with no significant interaction between different materials. There was a significant effect on cell proliferation and cytotoxicity with different exposure times (p < 0.0001) for each material. Cell proliferation rates were comparable for both cell lines at the beginning of the study, however, HGFB showed higher proliferation rates for all materials at day 10 with better proliferation activities with ZrO and m-PEEK (40.27%) and (48.38%) respectively. HGKC showed significant interactions (p < 0.0001) in cytotoxicity between different materials. Conclusion: The present in vitro assessment investigated the biocompatibility of different abutment materials with soft tissue cells (HGFB and HGKC). The findings suggest that m-PEEK and TiN are biologically compatible materials with human cells that represent the soft tissue and can be considered as alternative implant abutment materials to Ti and ZrO2, especially when the aesthetic is of concern.